2000
DOI: 10.1159/000018394
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Established and Healing Psoriasis

Abstract: Background: Previous studies have described apoptosis in the stratum granulosum and in the stratum corneum, but not in the germinative compartment in normal skin. In psoriasis, an increased epidermal apoptosis has been observed in the differentiated compartment, suggesting that apoptosis has a key role in the pathogenesis of psoriasis, as a counteracting factor to the overproduction of cells. Little is known on apoptosis in the germinative compartment. Methods: Apoptosis was studied on biopsies of normal skin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
2
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 11 publications
5
79
2
4
Order By: Relevance
“…So far, there has been little research on Bcl-2 expression in psoriatic epidermis. Most authors have concentrated on apoptosis of keratynocytes, but not lymphocytes [7,31]. Avramidis et al [32] found significant reduction in Bcl-2 and induction of apoptosis in endothelial cells of patients with psoriasis during etanercept treatment.…”
Section: Discussionmentioning
confidence: 99%
“…So far, there has been little research on Bcl-2 expression in psoriatic epidermis. Most authors have concentrated on apoptosis of keratynocytes, but not lymphocytes [7,31]. Avramidis et al [32] found significant reduction in Bcl-2 and induction of apoptosis in endothelial cells of patients with psoriasis during etanercept treatment.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, defects in epidermal apoptosis will result in hyperproliferation of keratinocytes, the underlying pathogenesis of psoriasis (Kawashima et al, 2004). Indeed, the apoptotic index of the basal cell layer in psoriatic epidermis (0.035%) is significantly lower than that of healthy skin (0.12%) (Laporte et al, 2000). Agents that induce keratinocyte apoptosis could therefore be useful in the treatment of psoriasis.…”
mentioning
confidence: 99%
“…The TUNEL method by TEM (TUNEL/TEM) was developed for retrospective studies using archival epoxyresin-embedded materials and enables the morphological discrimination of apoptotic cells among many cell types including necrotic or mitotic cells based on ultrastructural characteristics (Inoki et al 1997;Hayashi et al 1998;Otsuki 2000Otsuki ,2004. To date, several studies of psoriasis have shown that almost all proliferative keratinocytes are TUNEL positive, although psoriasis is a hyperproliferative disease (Laporte et al 2000). Our previous study of psoriasis by TUNEL/TEM (Kawashima et al 2004) clearly demonstrated that immunogold particles indicating the presence of free 39-OH DNA ends are localized on the nuclear euchromatin of cells in the S phase and, therefore, may actually label the site of physiological nicking yielded during DNA replication.…”
mentioning
confidence: 99%